2019
DOI: 10.1088/1748-9326/ab4291
|View full text |Cite
|
Sign up to set email alerts
|

Identifying multidisciplinary research gaps across Arctic terrestrial gradients

Abstract: Global warming is driving environmental change in the Arctic. However, our current understanding of this change varies strongly among different environmental disciplines and is limited by the number and distribution of field sampling locations. Here, we use a quantitative framework based on multivariate statistical modeling to present the current state of sampling across environmental disciplines in the Arctic. We utilize an existing database of georeferenced Arctic field studies to investigate how sampling lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 51 publications
(50 reference statements)
3
19
0
Order By: Relevance
“…As a result, it likely underestimates the full diversity of vegetation traits across the Arctic. Despite this limitation, the Kougarok Hillslope site adds to our understanding of tundra plant traits, which along with other arctic environmental measurements are often quantified in only a few locations in the world (Bjorkman et al, 2018;Metcalfe et al, 2018;Virkkala et al, 2019). The PFTs identified in our study matched well with trait-based classifications, particularly size-related traits, identified as covering most of the variability in arctic plant traits (Thomas et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As a result, it likely underestimates the full diversity of vegetation traits across the Arctic. Despite this limitation, the Kougarok Hillslope site adds to our understanding of tundra plant traits, which along with other arctic environmental measurements are often quantified in only a few locations in the world (Bjorkman et al, 2018;Metcalfe et al, 2018;Virkkala et al, 2019). The PFTs identified in our study matched well with trait-based classifications, particularly size-related traits, identified as covering most of the variability in arctic plant traits (Thomas et al, 2019).…”
Section: Discussionsupporting
confidence: 57%
“…As a result, it likely underestimates the full diversity of vegetation traits across the Arctic. Despite this limitation, the Kougarok Hillslope site adds to our understanding of tundra plant traits, which along with other arctic environmental measurements are often quantified in only a few locations in the world (Bjorkman et al, 2018;Metcalfe et al, 2018;Virkkala et al, 2019). The PFTs…”
Section: Discussionmentioning
confidence: 99%
“…Comparing our representativeness assessment with similar works shows a good match with results presented by Virkkala et al (2019), who also identified best data coverage for Fennoscandia and Alaska, while the overall patchy coverage in Siberia mainly focused on individual, densely instrumented research stations. Also a global network evaluation (Jung et al, 2020), based on a so-called extrapolation index as an indicator of expected error, shows a similar pattern, with Arctic errors generally at a high level, compared to the global average, but Canada and Siberia showing exceptionally high extrapolation uncertainties within the Arctic.…”
Section: Representativeness Assessmentsupporting
confidence: 85%
“…There have been several studies that aim at evaluating the spatial coverage of regional EC sites (Sulkava et al, 2011;Hoffman et al, 2013;Chu et al, 2021;Villarreal and Vargas, 2021) and for the atmospheric tall tower networks similar studies have been performed (Shiga et al, 2013;Ziehn et al, 2014;Kountouris et al, 2018), though none of these focused on the Arctic. Even though the patchiness of Arctic field sampling locations has received more attention lately (Metcalfe et al, 2018;Virkkala et al, 2019), so far only the distribution of Arctic chamber network has been extensively summarized (Virkkala et al, 2018). Thus, overall we find no detailed analysis of the Arctic EC network.…”
Section: Section 1: Introductionmentioning
confidence: 82%
“…Sites from other vegetation types, however, were less representative of the corresponding global climate space, with barren lands were masked out (Figure 3, right panel). More specifically, Arctic sites in SRDB have relatively narrow MAT and MAP coverage compared with the global Arctic MAT and MAP distribution, probably because many regions in the Arctic are covered by snow all year round, and thus it is difficult to measure RS in those sites (Virkkala et al, 2019). Desert SRDB sites have lower MAT but higher MAP than the global distribution,…”
mentioning
confidence: 99%